IMPLEMENTASI PROGRAM AKADEMI KELUARGA JABAR JUARA DALAM MENCEGAH CHILDREN STUNTING DI KABUPATEN SUMEDANG - Rika Kusdinar (LPPM UNSAP & FISIP UNSAP, 2022)
This study aims to examine the implementation of Akademi Keluarga Jabar Juara (AKJJ) program in children stunting in the Sumedang District Population Control and Family Planning Agency, the obstacles to its implementation, and efforts to overcome these obstacles. The method used in the preparation of this research report is a qualitative research method with a descriptive type. The sampling technique used was purposive sampling, with research informants: Head of Family Welfare Division, Staff of Family Welfare Division, and Head of Adolescent Reproductive Health Section (Family Planning). Data collection techniques through library research and field studies. In analyzing the data, the Miles and Huberman model used the following steps: data reduction, data presentation, conclusion drawing/verification, and triangulation. Based on the results of the study, it was concluded that the implementation of Akademi Keluarga Jabar Juara (AKJJ) program in children stunting at the Population Control and Family Planning Office of Sumedang Regency had been carried out in accordance with the provisions set out with a structured implementation flow through the formation of a family companion team made by DPPKB . However, in its implementation, currently experiencing several obstacles, including the lack of human resources in the program and some of the contents of the policy are not yet known by several target groups. In addition, another obstacle is that there are budget resources that are not yet available in every village where they still utilize the APBDes budget while the budget is limited. In overcoming these obstacles, several efforts were made, including holding clarifications or coordination meetings for policy clarity accompanied by training and information for both employees and target groups. And utilize the budget that will be used according to needs. Suggestions in connection with this research is to allocate people who focus on implementing the Akademi Keluarga Jabar Juara (AKJJ) program in every village/kelurahan so that in terms of accountability and equity it is clear so that the objectives of this program can be achieved.